Mr. Nice Guy [videorecording (DVD)] - Cheng, Long, 1954-; Norton, Richard, 1950-; Lee, Miki, 1977- (New Line Home Video, 1998)
When television chef Jackie's girlfriend is kidnapped and his apartment blown up, he takes action against the gang responsible.